Uji organoleptik, jamur, dan pH silase rumput pakchong yang diberi suplemen organik cair herbal - Ise Rahmawati; Nilawati Widjaja; Syifa Nurjannah; Sari Suryanah; Hilman Permana (University of Insan Cendekia Mandiri, 2024)
Pakchong grass is a high-yielding forage that has good quality and can be used as silage. The research aims to determine the physical quality, fungi, and pH of pakchong grass silage with the addition of herbal SOC. The variables observed were color, aroma, texture, taste, fungi, and pH. This research was carried out in Pulosari Village, Pangalengan District, Bandung Regency, West Java. This research used experimental methods and a Completely Randomized Design (CRD), consist of 4 treatments and 5 replications, namely: P1 = Pakchong grass + 1% herbal SOC, P2 = Pakchong grass + 3% herbal SOC, P3 = Pakchong grass + 5% herbal SOC, and P4 = Pakchong grass + 7% herbal SOC. The results showed that it had a significant effect on color, aroma, texture, taste, and fungi but had no significant effect on the pH of the silage. The higher the level of herbal SOC given, the more the quality decreases. The addition of 1% herbal SOC produced pakchong grass silage with the best physical, fungi, and pH qualities.